Pengaruh DBH, SILPA, Dan Jumlah Penduduk Terhadap Belanja Daerah Kabupaten/Kota Di Sumatera Selatan - Audri Olivia; Kiagus Zainal Arifin; Nurhasanah Nurhasanah (Jurnal Kendali Akuntansi, 2023)
The objective of this study is to assess the impact of Profit Sharing Funds (DBH), Overtime Calculation Budget (SiLPA), and Population Number (JP) on regional expenditure in the districts/cities of South Sumatra. This study utilizes secondary data as the primary source of information. The data is obtained from a comprehensive sample that encompasses all 13 districts and 4 cities within the South Sumatra province. The data covers a period of 5 years, specifically from 2016 to 2020. The population for this study comprises the budget implementation reports obtained from districts and cities in South Sumatra. This study employed various statistical techniques for data analysis, including descriptive statistical analysis, classical acceptance test, multiple linear regression test, and hypothesis testing. The software utilized for analysis was SPSS for Windows version 26. The research findings presented in this paper are incomplete in nature. The allocation of population and revenue sharing funds exhibits a noteworthy and statistically significant influence on regional expenditure patterns. The calculation of budget surplus (SiLPA) has a minimal and adverse effect on regional expenditure. In the context of regional spending, it is observed that Profit Sharing Funds (DBH), Budget Overtime (SiLPA), and Population Number (JP) exhibit a noteworthy and statistically significant influence.